Republic of Kosovo : Request for Stand-By Arrangement-Press Release; Staff Report; and Statement by the Executive Director for Republic of Kosovo. (IMF Staff Country Reports; Country Report ;, 2015)
EXECUTIVE SUMMARY Key issues: Kosovo faces the dual challenge of maintaining fiscal credibility and debt sustainability while shifting its growth model from one driven by remittances and consumption to one driven by investment and the tradable sector. This requires fiscal consolidation over the next two years that deflates unproductive current spending while increasing space for critical public investment and donor-financed capital projects. It also requires steps to further preserve financial stability, improve competitiveness, remove structural impediments to bank lending, and reduce corruption. Stand-By Arrangement (SBA): The authorities have requested a 22-month, SDR 147.5 million (250 percent of quota) SBA. An initial purchase of SDR 28.1 million would become available upon approval of this request. The program will seek to preserve low debt and financial stability and rebuild government bank balances while creating conditions for more dynamic and better-balanced growth. Specifically, policies would aim at: -- Strengthening public finances through fiscal consolidation, with the deficit path within the fiscal rule's limits. This will be supported by steps to improve budget composition and deflate unproductive current spending. Capital expenditure will be protected and even enhanced through the modification of the investment clause under the fiscal rule. A new debt limit will ensure that debt remains sustainable. -- Advancing financial sector reforms related to emergency liquidity assistance and risk-based supervision to bolster financial sector stability. -- Raising Kosovo's long-term growth prospects. Reforms will include the introduction of a public wage bill to boost competitiveness, a new public procurement process to improve the business environment, and steps to catalyze donor-project financing related to Kosovo's large development needs.